Nilai Perjuangan dalam Film Better Days (少年的你）Karya Derek Tsang - Rudiansyah Rudiansyah (Multilingual, 2021)
This research is entitled 'The Value of the Struggle in the Film Better Days (少年的你 ) by Derek Tsang.' The background of this research departs from an interest in literary works set in the struggle of a girl named Chen Nian who is preparing for her college entrance exam. The formulation of the research problem is what are the values of struggle in the Better Days film. The purpose of this study is to find, reveal and describe the formulation of the problem in its entirety and in detail. The research method used in this study is a qualitative descriptive method. The theory used in this research is the theory of sociology of literature according to Wellek and Warren. The data source used in this study is the film Better Days directed by Derek Tsang and released on October 25, 2019. The results of this study are the value of struggle and the influencing factors, in the film represented by several pieces of quotes and scenes. This film contains the values of struggle, including the value of helping; the value of courage; the value of self-sacrifice; the value of working together; the value of mutual respect; spirit, and never giving up. Keywords: better days; film; the value of struggle; Derek Tsang; China.